Neurological soft signs in mainstream pupils. Issue 5 (1st November 2001) - Fellick, J M; Thomson, A P J; Sills, J; Hart, C A
Abstract : AIMS: (1) To examine the relation between neurological soft signs and measures of cognition, coordination, and behaviour in mainstream schoolchildren. (2) To determine whether high soft sign scores may predict children with significant problems in other areas. METHODS: A total of 169 children aged between 8 and 13 years from mainstream schools were assessed. They form part of a larger study into the outcome of meningococcal disease in childhood. Half had previous meningococcal disease and half were controls. Assessment involved measurement of six soft signs followed by assessment of motor skills (movement ABC), cognitive function (WISC-III), and behaviour (Conners' Rating Scales). RESULTS: Children having an age corrected soft sign score above the 90th centile were considered to have an excess of soft signs. When compared to the other children they had significantly worse scores on the other three measures. Median movement ABC score was 15.3 v 7. Mean total IQ scores were lower by 10.3 points. Median behaviour scores were significantly higher on both parental and teacher questionnaires. A soft sign score above the 90th centile had a sensitivity of 38% for detecting cognitive impairment, 42% for detecting coordination problems, and 25% for detecting possible attention deficit hyperactivity disorder. CONCLUSION: In this group of children higher scores on the soft sign battery were related to significantly worse performance on measures of cognition, coordination, and behaviour. However, although soft sign assessment may be of interest it cannot accurately predict which children are likely to have impairment in other areas.